Catholic family towards holy perfection: pastoral challenges and management - Esti Susanti, Christina; Putra Adi Pratama, Alvarado; Suwito, Benny (Technium Social Sciences Journal, 2024)
This research examines Catholic families towards the perfection of holiness: challenges, management, and pastoral care. A Catholic family is a family based on Catholic marriage. The Catholic family itself is referred to as the ecclesia domestica or household church which has a special place in the Catholic Church. This research uses the literature study method. Literature study is research that focuses on searching and deepening supporting literature. Library sources are taken from Church documents that talk about the family and also other sources that support this research. The research results show that Catholic families face external and internal challenges. Therefore, the need to strengthen the foundation of the family in the environment and within the family itself is important in order to realize environment-based pastoral services, as is the pastoral focus of the Diocese of Surabaya. Researchers propose a family catechesis program which aims to build understanding, awareness and concrete action for families towards perfect holiness. This catechesis takes the form of a life catechesis that prioritizes everyday experiences interpreted in the light of the Gospel. This form or method of catechesis is carried out through family recollection in the environment.